Factors Associated with Student Feedback to Teachers in Quality Assurance in Iraqi Kurdistan - Rukhsar Muhammad Omar; Sarkawt Muhammad Qadir (Zanco Journal of Humanity Sciences)
Over the past few decades, the quality of education has emerged as a critical strategic concern in tertiary education institutions worldwide. University managers’ daily tasks now include comparing educational outcomes and rankings, for which quality assurance is significant. Quality assurance incorporates three separate but interdependent elements including student feedback to teachers, teacher portfolios, and continuous academic development. Student feedback concerns the quality and effectiveness of teaching and teacher performance. University instructors often complain about the grades and feedback they gain from students and reckon that the grades are based on students’ rate of success and teachers’ intimacy with students, rather than on teachers’ performances. Therefore, this study is devoted to investigating student feedback and the factors that determine the quality of feedback provided to instructors. To this intent, the study follows the principles of mixed methods in data collection and analysis; using self-reported questionnaires, instructor feedback scores in quality assurance, and student rates of success for each module as well as using IBM SPSS 25 and thematic analysis. The participants include university students and instructors selected from a public university in the Kurdistan Region of Iraq. The study assumes that three factors play a significant role in determining the level of feedback including the rate of success, instructors’ intimacy and rapport with students, and the quantity of material provided to students. The study concludes with far-reaching implications for higher education institutions in the Kurdistan Region of Iraq.